GE_GERICHTE P/23482/2017 vom 14. Januar 2019 - GE Cour de justice (2019)
LOI FEDERALE SUR LE STUPEFIANTS ET LES SUBSTANCES PSYCHOTROPES ; CONFISCATION (DROIT PENAL) | LStup.19; aCP.41.al1; CPP.267.al3; CPP.268.al1.leta; CPP.428.al3